Management work mode of college students based on emotional management and incentives - Ding, Xiang (Frontiers in Psychology, 2022)
The student management work model in colleges and universities is an effective plan for college student management, but the traditional college student management work is not very good, resulting in negative attitudes such as low learning desire, low learning efficiency, and inactive learning. In recent years, with the development of artificial intelligence technologies such as sentiment analysis and incentive theory, emotional management and incentive theory have been applied to the management of college students. The emotional management and incentive model is a way to help college students get rid of psychological obstacles and guide students to establish positive and correct values by analyzing the psychological information of college students and making corresponding feedback measures. This paper compares the college student management work model based on emotional management and incentives with the traditional college management work mode through experiments. The results show that the students' learning enthusiasm is better than the traditional college student management work mode based on emotional management and incentives. The student management work model in colleges and universities is 15.8% better, and the students' grades have improved by 12.5%; the college student management work model based on emotional management and incentives also has a positive role in helping students' mental health. The way of emotional management and motivation can make better use of college students' psychology to effectively manage students and guide students to develop in a good direction.